THE INDONESIA GOVERNMENT’S NEGOTIATION WITH THE GOVERNMENT OF SAUDI ARABIA IN PURSUIT OF INCREASING THE HAJJ QUOTA FOR 2025 - Madalia Faza (RADJA PUBLIKA, 2026)
This study analyzes the negotiation strategies and dynamics between Indonesia and Saudi Arabia concerning the proposed increase in Indonesia’s Hajj quota for 2025. As background, the research is motivated by Indonesia’s consistently high demand for Hajj pilgrimage—which exceeds the annual quota determined by the Saudi government—and the inconsistent outcomes of previous diplomatic efforts. While Indonesia successfully secured additional quotas in 2023 and 2024, similar success was not achieved for the 2025 Hajj season. The study employs a descriptive qualitative approach, collecting data through in-depth interviews, official documents, reports from the Indonesian Ministry of Religious Affairs, and relevant media publications. Data analysis was conducted interactively using the Miles and Huberman model. The findings indicate that the negotiation dynamics for 2025 were shaped by three main factors. First, Saudi Arabia implemented a strict evaluation of infrastructural capacity, particularly in the Mina–Arafah area. Second, the changes in Indonesia’s governmental structure following the 2024 election affected the continuity of technical diplomacy. Third, the stipulations outlined in the Hajj MoU for 1447 H/2026 AD emphasize that additional quota allocations can only be granted if Indonesia’s technical and operational preparedness meets Saudi standards. From a theoretical perspective, using Oran R. Young’s negotiation framework, these dynamics reveal a shift from interest-based negotiations (as seen in 2023–2024) to constraint-based negotiations in 2025. As a result, Indonesia was granted additional quota only for Hajj officers, not for regular pilgrims. The study concludes that the effectiveness of Hajj diplomacy is contingent upon institutional strength, continuity of technical-level negotiations, and adaptive strategic capacity in responding to evolving Saudi policies.